Alu insertion polymorphisms and susceptibility to metabolic syndrome in a Moroccan population - Hamid Farhane; Majida Motrane; Karchali Soufaine; Fatima-Ezzahra Anaibar; Aïcha Motrane; Said Nassor Abeid; Abderraouf Hilali; Nourdin Harich (Egyptian Journal of Medical Human Genetics)
Abstract Background Metabolic syndrome (MetS) is a multifaceted disorder that significantly elevates the cardiovascular disease risk. The diversity of the combination of its main components, conditioned by genetics and environmental risk factors, contributes to the complexity of this health condition and increases the difficulty of its diagnosis and treatment. Objective Our study aimed to explore the association between four Alu insertion polymorphisms and the risk of MetS as well as its components in the Doukkala population of Morocco. Methods A case–control study was conducted on 175 cases of MetS and 252 controls. Four Alu insertion polymorphisms (Alu-ACE, Alu-TPA25, Alu-PV92, and Alu-APOA1) were genotyped using Polymerase Chain Reaction followed by direct electrophoresis of its products. Results Our results showed that the Alu-PV92 and Alu-APOA1 Ins/Del polymorphisms are significantly associated with MetS, the patients are characterized by higher frequencies of genotype II (OR = 6.96, 95% CI [4.12–11.75], p < 0.0001) and *Ins allele for Alu-PV92, and DD genotype (OR = 3.32, 95% CI [1.57–7.00], p = 0.001) and *Del allele for Alu-APOA1 compared to controls. Additionally, a significant association was revealed with MetS in men carrying the *Ins allele and the Alu-TPA25 II genotype (OR = 2.11, 95% CI [1.00–4.44], p = 0.0487). Furthermore, our study concluded that the Alu polymorphisms analyzed were linked to several MetS components, such as hyperglycemia, obesity, hypertension, hyperglycemia, and abnormal lipid levels. Conclusion The Alu-PV92 and Alu-APOA1 Ins/Del polymorphisms were associated with an elevated MetS risk and its components in both women and men from the Doukkala population, while the Alu-TPA25 Ins/Del polymorphism are associated only in men with only some components. These findings hold considerable public health implications, indicating that Alu polymorphisms could serve as biomarkers for identifying individuals at risk of developing MetS.